1996
DOI: 10.1557/proc-449-319
|View full text |Cite
|
Sign up to set email alerts
|

TOF-LEIS Characterization and Growth of GaN Thin Films Grown with ECR and NH3

Abstract: GaN thin films were grown on various substrates by GSMBE using ECR nitrogen and ammonia. The growth of GaN was monitored by real time analysis, time of flight low energy ion scattering (TOF-LEIS) and RHEED.Growth of GaN on GaAs, ZnO, Ge and Al2O3 was investigated. The substrates’ surfaces were analyzed during pre-growth annealing and during GaN growth. The removal of surface contaminants and the modification of the surface stoichiometry from these surfaces are presented.GaN films on sapphire (0001) grown under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Others are using MSRI to monitor GaN thin film growth [33][34][35][36][37]. It has been shown that the Ga+/IT'_ MSRI ion ratio is indicative of rhe film quality.…”
Section: Red-time In Situ Tof-lsars Anaivsis Of Thin Film Depositionmentioning
confidence: 99%
“…Others are using MSRI to monitor GaN thin film growth [33][34][35][36][37]. It has been shown that the Ga+/IT'_ MSRI ion ratio is indicative of rhe film quality.…”
Section: Red-time In Situ Tof-lsars Anaivsis Of Thin Film Depositionmentioning
confidence: 99%
“…10,11 Since then, many more research groups have become interested and have initiated research using the technology. Device quality GaN, InGaN, and AlGaN thin films with growth rates as high as 1 m/h, with both n-and p-type doping, have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] GaN thin films have been grown with many different techniques such as metal-organic vapor phase epitaxy ͑MOVPE͒, chemical vapor deposition, and molecular beam epitaxy with nitrogen species generated via ion beams, plasma sources or NH 3 . [4][5][6] Chemical beam epitaxy ͑CBE͒ is a powerful technique that has an established record in the growth of complex III-V semiconductor heterostructures at low temperatures, with precise control of interfacial structure and material composition. 7 As a high vacuum growth technique, it is also compatible with in situ surface characterization tools such as reflection high energy electron diffraction ͑RHEED͒ and low energy ion scattering.…”
mentioning
confidence: 99%